THE EFFECT OF PICTURE AND PICTURE MODELS ON LEARNING RESULTS COMPARING IN NUMBERS CLASS II STUDENTS OF SDN 101 KOTA UTARA THE CITY OF GORONTALO - ISMAIL PIOKE; ZULWATI LAIYA (International Journal of Innovations in Engineering Research and Technology, 2021)
The purpose of this study is to determine the effect of using the picture and picture model on student learning outcomes in comparing whole numbers in grade II students of SDN 101 Kota Utara Kota Gorontalo. This type of research is quantitative descriptive research design with pre-experimental design, one group pretest posttest design. Sampling was done by saturated sampling where the sample was taken based on the entire population used. So that the sample in this study were all students of class II as many as 23 students. The data collection technique is done with the prerequisite ice: validity test, reliability test, normality test and hypothesis testing using tests.The results showed the average value before using the Picture and Picture model was 42.75 and after using the Picture and Picture model was 67.03. This is shown by the results of the t test, it is obtained tcount = 7,712 and ttable = 2,074 means tcount> ttable, H0 is rejected and Ha is accepted. Thus it is concluded that there is an effect of the use of the picture and picture model on student learning outcomes in comparing whole numbers in class II SDN 101 Kota Utara Kota Gorontalo